Current-Induced Reversible Resistance Jumps in La0.8Ca0.2MnO3 Microbridge*Supported by the National Natural Science Foundation of China under Grant Nos U1332205, 11404169 and 11274153, the Natural Science Foundation of Jiangsu Province under Grant No BK20140450, and the Huaian Science and Technology (Industry) Project under Grant No HAG2014043. (May 2016) - Zhai 翟, Zhang-Yin 章印; Xie 解, Qi-Yun 其云; Chen 陈, Gui-Bin 贵宾; Wu 吴, Xiao-Shan 小山; Gao 高, Ju 炬
Abstract : Two spatially confined La0.8 Ca0.2 MnO3 (LCMO) microbridges with different widths, starting from a single LCMO film (3 mm×5 mm), are fabricated by optical lithography. A second new and robust metal-insulator transition (MIT) peak at about 75 K appears, in addition to the normal MIT at 180 K observed in the standard LCMO film. When the two bridges are processed by currents of high densities, interesting reversible resistance jumps are excited only around the new peak. A stronger dependence of resistance jump on current excitation is found for the bridge with a smaller width. The temperature driven transition between new excited multiple metastable states are involved to explain the interesting low-temperature ultra-sharp jumps.